Post-fire recovery occurs overwhelmingly by resprouting in the Chaco Serrano forest of Central Argentina - Torres, Romina Cecilia (2014)
In fire-prone landscapes, differences in post-fire regeneration by resprouting between species or sitescould be far more important in explaining vegetation physiognomy and composition than seed regeneration. Thisis the first study exploring the relative contribution of tree resprouts and seeds to post-fire crown volume in theChaco Serrano forest of South America. Additionally, we compare the resprouting response among species andquantify post-fire changes in tree composition among sites.We established 290 permanent plots distributed in threesites affected by wildfires in 2005. For all tree species in all plots we recorded survival of every individual 1 year afterthe fire; at the plot level, we recorded the above-ground tree volume before and 3 years after the fire. Resproutingfrom the base was the main resprouting type. Survival varied between species from 73% to 100% for native speciesand from 7% to 100% for non-natives. Before the fire, crown volume was similar in the three sites, and wascompletely lost after the fire in 92% of the plots.Three years after the fire, between 8% and 58% of crown volumewas recovered. The ratio of crown recovery because of resprouts and seedlings was 1562:1. Tree compositionexhibited few changes because of the high post-fire survival of most native species.We conclude that in the semiaridChaco Serrano ecosystem tree species regenerate mainly by resprouting. This regeneration mode should be takeninto account to better understand post-fire successional pathways of these forests, their management and therestoration of burnt forest areas.